Regional differences in the prevalence of obstetric complications in relation to maternal obesity and food purchases - Outi Pellonperä; Jelena Meinilä; Jaakko Nevalainen; Heidi Sormunen‐Harju; Johanna Metsälä; Mika Gissler; Mikael Fogelholm; Maijaliisa Erkkola; Hannu Saarijärvi; Saila Koivusalo (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Regional variations exist in the prevalence of type 2 diabetes and cardiovascular disease in Finland. As these conditions share risk factors with major obstetric complications, we aimed to investigate whether there are geographical differences in the prevalence of pregnancy complications and if these differences could be explained by known risk factors such as maternal obesity or dietary intake. Material and Methods In this observational study, data from the Finnish Medical Birth Register and the Hospital Discharge Register were analyzed for primiparous women who had singleton births in Finland from 2013 to 2017. We calculated regional prevalence rates of gestational diabetes, gestational hypertension, preeclampsia, and premature birth. Loyalty card data from the largest food retailer were utilized to assess the regional average of food purchases of fertile‐age women living in single‐ or two‐adult households between September 2016 and December 2017. The datasets were merged by postal codes and organized by cardinal direction regions. Results The birth register included 109 306 women, and data from 3937 purchasers were analyzed. Compared with women living in Southern Finland, those living in the North had higher odds for gestational hypertension (adjusted OR 1.36, 95% CI 1.10–1.68, p = 0.005), while women living in Eastern Finland had greater odds for preeclampsia (adjusted OR 1.21, 95% CI 1.02–1.44, p = 0.030). We did not find regional differences in the prevalence of gestational diabetes or preterm birth. Higher average areal fiber content of the purchases decreased the odds of gestational hypertension (OR 0.90, 95% CI 0.89–0.99, p = 0.022), and diminished gestational hypertension's geographical disparity. Higher means in areal red and processed meat purchases were associated with preterm birth (OR 1.29, 95% CI 1.02–1.62, p = 0.031), and a high maternal body mass index was related to all pregnancy complications (OR 1.3–9.8, p < 0.001 in all comparisons), but they did not account for regional differences. Conclusions Compared with Southern Finland, hypertensive pregnancy complications were more prevalent in women living in Eastern and Northern Finland. Obesity did not explain regional differences, whereas lower fiber content of purchases in these regions may have contributed to the prevalence of pregnancy hypertension.